Transformative driven mechanism framework as key success indicators for blended learning - Mahmud, Malissa Maria (2017)
Current literature shows that blended learning has inevitably permeated and transformed the landscape of educational practices. However, in the same vein, it also depicts less consideration given to the impending gaps in the blended learning experience, consequently indicating a paucity of evidence in the context of these technological interventions. This study aimed to examine and identify the Key Success Indicators (KSIs) for blended learning approaches. The research is delineated in seven research questions postulated to address the overall facets in blended learning: the powerful and the combined Effect Sizes (ESs), the definitions of blended learning, the types of technological intervention, the specific ratio or percentage of intervention, and the quality of indicators determined in the language related blended learning studies and other subjects related to blended learning studies. These research questions have guided this study to probe into the magnitude and power of ESs yielded from the 96 included samples by employing meta-analysis as an instrument of analysis. In addition to the ESs, this study also aimed to determine the key facets in blended learning approaches wherein the qualitative content analysis method was employed to analyse the samples. Besides that, two novel approaches were also employed as part of the data analysis to examine the categories of technological interventions and ratio of technology versus traditional approaches. The means of analyses enabled vital insights about the critical success indicators in a blended learning environment. Specifically, the findings from the seven research questions outline the KSIs as quantifiable measurements and guidelines in implementing the proposed Transformative Driven Mechanism (TDM) Framework that the researcher firmly believes possesses tremendous transformative potential in augmenting the quality of students’ learning experience and ultimately reshaping the entire teaching and learning landscape.